Teaching Middle School Students About Structural Racism with Trevor Noah’s “Born a Crime” - Almanssori, Salsabel (Radical Teacher, 2022)
While Noah’s stories reveal the realities of racialized and classed oppression in post-apartheid South Africa, empowerment is at the heart of his narrative as he centers acts of resistance, particularly when discussing his mother. Storying these acts of resistance allowed my students to see that where there is oppression, there are always people who fight, who are agents of change and empowerment for themselves and their communities.